Tuberculin skin test – Outdated or still useful for Latent TB infection screening? - Gualano, Gina; Mencarini, Paola; Lauria, Francesco Nicola; Palmieri, Fabrizio; Mfinanga, Sayoki; Mwaba, Peter; Chakaya, Jeremiah; Zumla, Alimuddin; Ippolito, Giuseppe (International journal of infectious diseases, 2019)
•Tuberculin skin test (TST) is over a century old but it continues to be used widely.•When IGRAs were introduced it was anticipated that they would rapidly replace TST.•Neither TST nor IGRAs have a high accuracy for predicting active TB.•Latest WHO recommendations are that either TST or IGRA can be used to test for LTBI.•TST will be clinically useful until more accurate tests become available. To make an informed viewpoint on the usefulness of Tuberculin Skin test (TST) compared to Interferon Gamma Release Assays (IGRAs) for diagnosis of Latent TB Infection (LTBI) in different geographical settings. We reviewed the current literature on TST compared to IGRA, including national implementation of WHO LTBI recommendations and retrospective data over the past 7 years at the National Institute for Infectious Diseases “L. Spallanzani” as indirect indicator of usage of both tests under actual programmatic conditions. Current national guidelines vary considerably, reflecting the uncertainty and rapidly evolving evidence about the potential use of these tests. Data from Institute “L. Spallanzani” showed IGRA concordance in TST positive subjects only in 54.74% of subjects, while there was strong concordance between two tests in TST negative subjects (93.78%). Neither IGRAs nor TST can distinguish active TB from LTBI. TST will continue to be clinically useful in low and high TB endemic areas until more accurate and predictive tests will become available. Clinical judgment remains fundamental in choosing between IGRA/TST tests and interpreting their results.